Gubernatorial Power and the Struggle for Executive Efficiency in Twentieth Century Maine - Mills, Paul (Maine Policy Review, 2002)
In this commentary, Paul Mills discusses the balance between the executive and legislative branches of Maine state government in the twentieth century, noting that from 1986 to the time of the writing of this commentary (2002), the state’s governors have had a different political affiliation than the legislatures elected to serve with them. He remarks that even as the mechanics of government have become more efficient through reforms, Maine people have created and enforced a system that puts the governor and legislature at odds, hampering their ability to move forward.